2010
DOI: 10.1177/0091270009344986
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics and Pharmacodynamics of a Bolus and Infusion of Cangrelor: A Direct, Parenteral P2Y12 Receptor Antagonist

Abstract: The purpose of this study is to evaluate the safety, tolerability, pharmacokinetics, and pharmacodynamics of cangrelor administered as an intravenous bolus plus a continuous infusion in healthy volunteers. Twenty-two healthy volunteers are randomized to receive 1 of 2 intravenous cangrelor dosing regimens: a 15-microg/kg bolus followed by a 2-microg/kg/min infusion or a 30-microg/kg bolus followed by a 4-microg/kg/min infusion. The infusion is continued for 60 minutes, and serial blood samples are obtained for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
120
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 141 publications
(128 citation statements)
references
References 14 publications
3
120
0
1
Order By: Relevance
“…Increasing the concentration of clopidogrel or prasugrel AM demonstrated that they have a limited ability to compete with cangrelor (1000 um/L) for binding to the P2Y 12 receptor. The data suggests that prasugrel AM may be better able to compete with cangrelor than clopidogrel AM despite both thienopyridine AMs having similar IC 50 values (0.30 mol/L) [16].…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Increasing the concentration of clopidogrel or prasugrel AM demonstrated that they have a limited ability to compete with cangrelor (1000 um/L) for binding to the P2Y 12 receptor. The data suggests that prasugrel AM may be better able to compete with cangrelor than clopidogrel AM despite both thienopyridine AMs having similar IC 50 values (0.30 mol/L) [16].…”
Section: Discussionmentioning
confidence: 99%
“…Cangrelor is a rapidly acting, direct-binding, reversible, intravenous P2Y 12 antagonist, which makes it attractive for use during percutaneous coronary intervention (PCI) in patients who may not have been sufficiently pretreated with an oral P2Y 12 antagonist, such as may occur in the management of acute ST-segment elevation myocardial infarction (STEMI) [1,2]. In the recent CHAMPION PHOENIX study, a bolus plus 2 hour infusion of cangrelor resulted in a decrease in ischaemic events during PCI with no increase in severe bleeding [3].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations